Clotting test results correlate better with DOAC concentrations when expressed as a "Correction Ratio"; results before/after extraction with the DOAC Stop reagent. Issue 179 (July 2019) - Exner, T.; Favresse, J.; Lessire, S.; Douxfils, J.; Mullier, F.
Abstract: Introduction: Clotting test results are currently not useful for estimating direct oral anti-coagulant (DOAC) concentrations because baseline results vary. DOAC Stop is a DOAC extracting agent with no effect on clotting factors. We investigated if aPTT (activated partial thromboplastin time) and dRVVT (dilute Russells viper venom time) results might correlate better with DOAC concentrations if results after DOAC extraction were used to estimate a "before/after" value (Correction Ratio). Materials and methods: We used activated partial thromboplastin time (aPTT, PTT-LA) and dilute Russells viper venom time clotting test (dRVVT) results previously recorded on DOAC patient plasmas (25 dabigatran, 15 apixaban, 19 rivaroxaban) without known thrombotic risk factors before and after DOAC extraction. DOAC concentrations had been determined by standard chromogenic assays. Results: Correlations between aPTT and dabigatran, apixaban, and rivaroxaban concentrations were initially poor (0.64, 0.15 and 0.39 respectively). However, they improved significantly to 0.94, 0.89 and 0.80 when the ratios of initial aPTT to the aPTT obtained after DOAC extraction were plotted against DOAC concentration. Still better correlations (0.99, 0.97, 0.95) and much higher sensitivities to the DOACs were obtained when dRVVT (LA Confirm) tests were used following this procedure on the same samples. Conclusions: The correlations of aPTT and dRVVT tests with DOAC concentrations were significantly improved by using the ratio of result "before" to those "after" DOAC extraction. The results indicate that dRVVT (especially LA Confirm) and similar tests might be useful for determining DOAC concentrations more reliably and with better sensitivity than currently possible with clotting tests. Highlights: Extraction of DOACs by DOAC Stop allows baseline clotting test results to be estimated The "Correction Ratio" is the clotting test result before divided by that after DOAC extraction. The CR correlated much better with DOAC concentration than initial results. The best test for this was high phospholipid dRVVT reagent. This procedure permits quick estimation of DOACs from simple clotting tests via appropriate calibration curves.